Non-agrocultural co-peratives and economy transformation in Cuba: politic processes and strategies - Vuotto, Mirta (REVESCO. Revista de Estudios Cooperativos, 2015)
Contribution of co-operatives has been demonstrated since the 1970s as the main development line in agricultural production in Cuba. In contrast, there has been a late recognition of urban co-operatives, even if the need of transformations based on the realization of property in different territorial scenarios had been identified. The article analyses the reform processes launched since the first decade of the 21st century focusing on the nature of the initiatives fostering formation and promotion of nonagricultural co-operatives including follow up of their performance. The potential and limitations of the recent experiences are examined in order to reflect on the organizational processes and transformations from the point of view of their members. To conclude, some questions are posed about whether these co-operatives are capable of avoiding the impact of earlier employment circumstances and of developing strategies aimed at reinforcing voluntary membership and autonomy on which they are founded.
Keywords: Non-Agricultural Cooperatives; Economic Reforms; Urban Cooperatives; New Cuban Cooperativism.